2020
DOI: 10.1007/s10354-020-00741-6
|View full text |Cite
|
Sign up to set email alerts
|

New developments in the management of achondroplasia

Abstract: Achondroplasia is the most common form of disproportionate short stature. A dominantly inherited FGFR3 mutation permanently activates the fibroblast growth factor receptor 3 (FGFR3) and its downstream mitogen-activated protein kinase (MAPK) signalling pathway. This inhibits chondrocyte differentiation and puts a break on growth plate function, in addition to causing serious medical complications such as foramen magnum and spinal stenosis and upper airway narrowing. A great deal has been learned about complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 47 publications
(48 reference statements)
0
15
0
1
Order By: Relevance
“…Establishing the natural history of the condition is essential in rare diseases to avoid uncertainty regarding the optimal timing of intervention, incorrectly attributing side effects to the study drug rather than as disease-related complications (or vice versa ), and misunderstanding which are the best outcome measures. 18 Specifically, by establishing AHV in PROPEL, each child’s change in AHV in PROPEL 2 following infigratinib treatment can be compared with PROPEL data, allowing each child to act as their own control. Therefore, natural history observational studies, such as PROPEL, facilitate the assessment of outcomes of greatest relevance to individuals with a specific condition and rigorous assessment of safety data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Establishing the natural history of the condition is essential in rare diseases to avoid uncertainty regarding the optimal timing of intervention, incorrectly attributing side effects to the study drug rather than as disease-related complications (or vice versa ), and misunderstanding which are the best outcome measures. 18 Specifically, by establishing AHV in PROPEL, each child’s change in AHV in PROPEL 2 following infigratinib treatment can be compared with PROPEL data, allowing each child to act as their own control. Therefore, natural history observational studies, such as PROPEL, facilitate the assessment of outcomes of greatest relevance to individuals with a specific condition and rigorous assessment of safety data.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, natural history observational studies, such as PROPEL, facilitate the assessment of outcomes of greatest relevance to individuals with a specific condition and rigorous assessment of safety data. 18 …”
Section: Discussionmentioning
confidence: 99%
“…As novel pharmacological therapies emerge, early and complete diagnosis of achondroplasia in the childhood population will facilitate earlier access to treatment and provide potential benefits for the growth of the base of the skull and spinal canal in particular, which are both impacted by early synchondrosis closure in this condition (Högler & Ward, 2020). We are hopeful this may avoid early craniocervical surgery and some of the more burdensome spinal symptoms experienced by our current patients.…”
Section: Discussionmentioning
confidence: 99%
“…Authors reported that RBM-007 rescued the impaired differentiation and maturation of chondrocytes and restored defective skeletal growth in a mouse model of achondroplasia [ 89 , 90 ]. RBM-007 is in a Phase 1 study to evaluate its safety, tolerability and pharmacokinetics (JapicCTI-205345).…”
Section: Methods Of Treatmentmentioning
confidence: 99%